Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Long-spined black sea urchin - Ogden, John C. (U.S. Department of the Interior, 1987)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.77)